[Rezension von: Yijiang Zhong, The origin of modern Shinto in Japan] - Andreeva, Anna (The American historical review, 2018)
The newly established Bloomsbury Shinto Studies book series continues to yield interesting research cases. Until recently in the Western imagination, Shinto was
Gesehen am 25.05.2020
Keywords: Rezension